Individual behavioural counselling for smoking cessation. - Lancaster, T; Stead, L (2005)
BACKGROUND: Individual counselling from a smoking cessation specialist may help smokers to make a successful attempt to stop smoking. OBJECTIVES: The objective of the review is to determine the effects of individual counselling. SEARCH STRATEGY: We searched the Cochrane Tobacco Addiction Group Specialized Register for studies with counsel* in any field. Date of the most recent search: December 2004. SELECTION CRITERIA: Randomized or quasi-randomized trials with at least one treatment arm consisting of face-to-face individual counselling from a healthcare worker not involved in routine clinical care. The outcome was smoking cessation at follow up at least six months after the start of counselling. DATA COLLECTION AND ANALYSIS: Both authors extracted data. The intervention and population, method of randomization and completeness of follow up were recorded. MAIN RESULTS: We identified 21 trials with over 7000 participants. Eighteen trials compared individual counselling to a minimal behavioural intervention, four compared different types or intensities of counselling. Individual counselling was more effective than control. The odds ratio for successful smoking cessation was 1.56 (95% confidence interval 1.32 to 1.84). In a subgroup of three trials where all participants received nicotine replacement therapy the point estimate of effect was smaller and did not reach significance (odds ratio 1.34, 95% confidence interval 0.98 to 1.83). We failed to detect a greater effect of intensive counselling compared to brief counselling (odds ratio 0.98, 95% confidence interval 0.61 to 1.56). AUTHORS' CONCLUSIONS: Smoking cessation counselling can assist smokers to quit.